2015
DOI: 10.7197/cmj.v37i1.5000071890
|View full text |Cite
|
Sign up to set email alerts
|

The scolocidal effect of propolis on protoscoleces and daugther cysts

Abstract: SUMMARYObjective: Scolocidal elements are used in the aim of not scattering the protoscoleces' outside the cyst during the treatment of cyst hydatid in our present-day. It is hoped from the scolocidal materials; besides its effect on protoscoleces, not being toxic, being easy practicable, not causing sclerozan cholanjit and if possible, penetrating in the daughter vesicules. In this research, the effect of propolis which is a bee product on protoscoleces were investigated. Methods: In our work, daughter vesicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…[42] Özcelik et al (2015) also determined that propolis can act on daughter vesicles within 10 min. [43] In addition, Karaman et al (2022) reported that the Cystoseria barbata, a brown algae, can be used as a scolicidal agent, while Yücel (2022) reported the same for Cystoseira crinita, which is also a brown algae. [22,23] It was observed that the scolicidal effect of organic solvent extracts of U. rigida prepared in chloroform, dichloromethane, hexane and methanol increased over time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[42] Özcelik et al (2015) also determined that propolis can act on daughter vesicles within 10 min. [43] In addition, Karaman et al (2022) reported that the Cystoseria barbata, a brown algae, can be used as a scolicidal agent, while Yücel (2022) reported the same for Cystoseira crinita, which is also a brown algae. [22,23] It was observed that the scolicidal effect of organic solvent extracts of U. rigida prepared in chloroform, dichloromethane, hexane and methanol increased over time.…”
Section: Resultsmentioning
confidence: 99%
“…(2007) reported that Allium sativum was effective on protoscoleces at 50 mg/mL concentration of at the 15th min. [42] Özcelik et al (2015) also determined that propolis can act on daughter vesicles within 10 min. [43] In addition, Karaman et al (2022) reported that the Cystoseria barbata, a brown algae, can be used as a scolicidal agent, while Yücel (2022) reported the same for Cystoseira crinita, which is also a brown algae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozcelik et al [53] reported that Allium sativum was effective on protoscolices. Again, Ozcelik et al [54] found that propolis also affected daughter vesicles within 10 minutes. In the study, the M extract of C. crinita showed no live parasites at the 7th hour.…”
Section: Discussionmentioning
confidence: 98%
“…Ozcelik et al [ 53 ] reported that Allium sativum was effective on protoscolices. Again, Ozcelik et al [ 54 ] found that propolis also affected daughter vesicles within 10 min. In the study, the M extract of C. crinita showed no live parasites at the 7th h. Additionally, the DCM extract showed no parasites at the 9th h. No viable protoscolices were observed at the 11th h for the Ch and H extracts.…”
Section: Discussionmentioning
confidence: 99%